2016
DOI: 10.1534/g3.115.019265
|View full text |Cite
|
Sign up to set email alerts
|

Neurons That UnderlieDrosophila melanogasterReproductive Behaviors: Detection of a Large Male-Bias in Gene Expression infruitless-Expressing Neurons

Abstract: Male and female reproductive behaviors in Drosophila melanogaster are vastly different, but neurons that express sex-specifically spliced fruitless transcripts (fru P1) underlie these behaviors in both sexes. How this set of neurons can generate such different behaviors between the two sexes is an unresolved question. A particular challenge is that fru P1-expressing neurons comprise only 2–5% of the adult nervous system, and so studies of adult head tissue or whole brain may not reveal crucial differences. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 89 publications
(138 reference statements)
16
43
0
Order By: Relevance
“…We argue here that Fru M alters expression of distinct genes across fru subpopulations, and that these transcriptional differences are masked when the whole fru populations are analyzed by RNA-seq. However, a previous study identified genes enriched in male fru+ neurons in adult by TRAP (65). We were somewhat surprised to find that we did not re-discover these genes, especially as our analysis is more sensitive than TRAP (i.e.…”
Section: Comparison With Previous Genome-wide Datasetsmentioning
confidence: 73%
“…We argue here that Fru M alters expression of distinct genes across fru subpopulations, and that these transcriptional differences are masked when the whole fru populations are analyzed by RNA-seq. However, a previous study identified genes enriched in male fru+ neurons in adult by TRAP (65). We were somewhat surprised to find that we did not re-discover these genes, especially as our analysis is more sensitive than TRAP (i.e.…”
Section: Comparison With Previous Genome-wide Datasetsmentioning
confidence: 73%
“…This indicates that the sexually dimorphic functions of these factors do not end when the sexually dimorphic elements of the nervous system complete their development. 83,87,102,[113][114][115] That the sex determination pathway continues functioning into adulthood to drive behavior is also supported by studies in Drosophila, which show that the genetic feminization of specific elements in the olfactory system of adult males is associated with same-sex male courtship behavior. 116,117 Furthermore, postdevelopmental genetic manipulations of the sex-specific splicing complex tra and tra-2 ( Figure 1A), for example, can induce male-like courtship behaviors in biological females.…”
Section: Sex Determination At the Cellular And Molecular Levelsmentioning
confidence: 89%
“…In particular, it appears that the fru locus confers a sexual identity to developing neurons underlying adult courtship behaviors, presumably by acting as a transcriptional switch to turn on or off sexspecific patterns of gene expression that ultimately shape sex-specific neural circuits. 37,45,[77][78][79][82][83][84][85][86][87] Although not as well described at the molecular and cellular levels, many animal species have evolved sex determination mechanisms that do not necessarily depend on sexually dimorphic developmental pathways (Figure 2). For example, some animal species can switch between male-and female-specific behaviors and physiology as sexually mature adults.…”
Section: Sex Determination At the Cellular And Molecular Levelsmentioning
confidence: 99%
“…This complicates assessments of isoform abundance and gene expression when using short-read RNA-seq data. In the past, an exonic region was quantified without regard to differences in donor/acceptor sites (Dalton et al 2013;Graze et al 2014;Newell et al 2016;Fear et al 2016) to avoid double counting reads, and in regions where differences are small (less than 10 bp) there is no meaningful loss of information in this approach. However, the overlap is often much larger than this, so to address this issue we use a classification scheme where reads may be assigned to exons, exonic regions, or exon fragments.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…We take an approach here that is sensitive to both expression differences within isoforms and between isoforms, in so far as the two can be decomposed ( Fig. 1a) (Dalton et al 2013;Newell et al 2016;Fear et al 2016). The accurate identification of a particular isoform with short-read RNA-seq requires that at least one exon or splicing event be unique to that isoform, however, this is usually not the case.…”
mentioning
confidence: 99%